2014
DOI: 10.5120/19020-0504
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Identifying Comparative Sentences

Abstract: Comparative sentences are used to express the explicit classifications between two entities with respect to the degree or quantity to which they possess some gradable property. Identifying the comparative sentences is a challenging task. This gives a new research direction for the researches. In this paper various approaches which were used for the identification of the comparative sentences in the text documents are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Saritha and Pateriya [15] studied various methods for comparative sentence identification and classification. They found that few studies had been conducted on comparative sentences, and they used different supervised and unsupervised techniques to identify the comparative sentences and relations.…”
Section: Text Classificationmentioning
confidence: 99%
“…Saritha and Pateriya [15] studied various methods for comparative sentence identification and classification. They found that few studies had been conducted on comparative sentences, and they used different supervised and unsupervised techniques to identify the comparative sentences and relations.…”
Section: Text Classificationmentioning
confidence: 99%
“…Some studies also used machine learning method to carry out experiments [8], [9]. Saritha et al [10] summarized the techniques used to identify the comparative sentences from text documents. From pattern matching to machine learning, the results of Jindal et al revealed that most of the techniques still need numerous manual annotations, and their performance requires further improvement.…”
Section: Comparative Sentences Identificationmentioning
confidence: 99%
“…SVM (support vector machine) is one of text classification methods that is known to have high performance among many other classifiers [4]- [6]. On the other hand, Naïve Bayes is a classifier that is a simple and easy to implement [7].…”
Section: Introduction a Backgroundmentioning
confidence: 99%